Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province. Rapport soumis au Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire) - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire). Rapport soumis au Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019b

The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). Submitted to the Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019c

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.